Vibration Characteristics of Heavy-Duty CNC Machine Tool-Foundation Systems - Yang Tian; Qilin Shu; Zhifeng Liu; Yujie Ji (Shock and Vibration)
Vibration characteristics of heavy CNC machine tools are directly affected by their foundations. To analyze vibrations of heavy CNC machine tools caused by internal and external loads, a system dynamics model of a rigid-flexible coupled heavy-duty CNC machine tool-foundation system was established based on the multibody transfer matrix method. Since joint surfaces can seriously affect the accuracy of system mechanics models, the substructure synthesis method was first used to establish a dynamic model of the joint surface. The frequency response function was then used to identify model parameters. Moreover, to improve the accuracy of parameter identification of the joint surface, a residual frequency compensation function was used to reconstruct the frequency response function. Finally, the multibody system model was implemented by combining surface elements. To verify the system dynamics model, an experimental model of the heavy-duty machine-foundation system was built, taking into consideration joint surface factors, and the theoretical model was validated by comparing theoretical, simulation, and experimental results. Using the theoretical model, the influence of different forms of concrete foundations, materials, and soil properties on the vibration characteristics of heavy-duty CNC machine tools was analyzed, thus providing a theoretical basis for optimizing and improving CNC machine tools.